Utilization of School Resources for Science Learning in Early Childhood Education: A Systematic Literature Review - Siti Sumarni; Asma Kurniati; la Jeti (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Optimal utilization of school resources is the key to providing concrete and meaningful science learning for early childhood. This study aims to systematically review the literature on strategies for utilizing school environmental resources to develop science learning in Early Childhood Education (ECE). The method employed is a Systematic Literature Review (SLR) using the PRISMA protocol, sourcing data from SINTA 1-3 accredited journals such as Jurnal Murhum, Obsesi, UNJ, Undiksha, and UIN Sunan Kalijaga. Out of 516 identified articles, 9 met the inclusion criteria (2019–2025) for further analysis. The findings indicate that utilized school resources fall into three main categories: the physical environment (school grounds and coastal ecosystems), biotic components (plants and trees), and abiotic components (natural loose parts). Integrating these resources through Contextual and STEAM approaches has proven effective in enhancing children's cognitive abilities, naturalist intelligence, and environmental literacy (eco-literacy). This study offers practical implications suggesting that financial constraints are not barriers; teacher creativity in transforming school environmental facilities into real laboratories can create profound learning experiences. This research is expected to serve as a policy reference for school principals in organizing learning ecosystems and as a guide for teachers to reduce reliance on manufactured media.